Waste heat recovery from aluminum production - Yu, Miao, 1992- (2018)
Around half of the energy consumed in aluminum production is lost as waste heat. Approximately 30-45% of the total waste heat is carried away by the exhaust gas from the smelter which is the most easily accessible waste heat stream. Alcoa Fjardaal in east Iceland produces 350 000 tons annually, emitting the 110 °C exhaust gas with 88.1 MW of heat. This work concentrates on creating and comparing models of low-temperature energy utilization from the aluminum production. Three scenarios, including organic Rankine cycle (ORC) system for electric power production, heat supply system and combined heat and power (CHP) system, were proposed to recover waste heat from the exhaust gas. The electric power generation potential is estimated by ORC models. The maximum power output was found to be is 2.57 MW for an evaporation temperature of 61.22°C and R-123 as working fluid. 42.34 MW can be produced by the heat supply system with the same temperature drop of the exhaust gas in the ORC system. The heat requirement to supply heat to a district heating system for the local community can be fulfilled by the heat supply system. There is a potential opportunity for agriculture, snow melting and other industrial applications with the heat supply system. The CHP system is more comprehensive. 1.156 MW power and 23.55MW heating capacity can be produced by CHP system. The highest energy efficiency is achieved by the heat supply system and the maximum power output can be obtained with the ORC system. In the power generation system, the efficiency of organic Rankine cycle is significantly limited by the low temperature of the exhaust gas. It would be possible to improve the efficiency of the ORC by increasing the heat source temperature. The temperature of the heat source can be raised by reducing the dilution air from the environment into the pot. The heat balance of the smelter is studied. The positive result is found, that the efficiency of the cycle and power output are effectively improved, and a good trend of the system ...